CPT443 – Automata Theory & Formal Languages (Teori Automata & Bahasa Formal) - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 2021)
Second Semester Examination 2020/2021 Academic Session July 2021 CPT443 – Automata Theory & Formal Languages (Teori Automata & Bahasa Formal) Duration : 2 hours (Masa : 2 jam)